A 12-month prospective, observational study of treatment regimen and quality of life associated with ADHD in central and eastern europe and eastern Asia - Goetz, Michal; Yeh, Chin-Bin; Ondrejka, Igor; Akay, Aynur; Herczeg, Ilona; Dobrescu, Iuliana; Kim, Boong Nyun; Jin, Xingming; Riley, Anne W; Martényi, Ferenc; Harrison, Gavan; Treuer, Tamás (Journal of attention disorders, 2012)
OBJECTIVES: This prospective, observational, non-randomized study aimed to describe the relationship between treatment regimen prescribed and the quality of life (QoL) of ADHD patients in countries of Central and Eastern Europe (CEE) and Eastern Asia over 12 months. METHODS: 977 Male and female patients aged 6-17 years seeking treatment for symptoms of ADHD were assessed using the Child and Adolescent Symptom Inventory-4 Parent Checklists, and the Clinical Global Impressions-ADHD-Severity scale. QoL was assessed using the Child Health and Illness Profile-Child Edition parent report form. Patients were grouped according to whether they were prescribed psycho- and/or pharmacotherapy (treatment) or not (no/'other' treatment). RESULTS: No statistically significant differences were observed between cohorts (treatment vs. no/'other' treatment) in terms of change in QoL, although there was improvement over 12 months, with a greater improvement experienced by patients in the treatment cohort in both study regions (CEE and Eastern Asia). Psychoeducation/counselling and methylphenidate were the predominant ADHD treatments prescribed. CONCLUSIONS: Although both treatment and no/'other' treatment cohorts showed improvements in mean QoL over 12 months, the difference was small and not statistically significant. A major limitation was the higher than anticipated number of patients switching treatments, predominantly from the no/'other' treatment cohort.
Keywords: výsledek terapie; Europe, Eastern; Male; kvalita života; Quality of Life; Counseling; Dálný východ; Adolescent; Child; dítě; Prospective Studies; mužské pohlaví; Methylphenidate; mladiství; Attention Deficit Disorder with Hyperactivity; Central Nervous System Stimulants; hyperkinetická porucha; Treatment Outcome; Asia, Eastern; stimulanty centrálního nervového systému; lidé; ženské pohlaví; Humans; methylfenidát; východní Evropa; poradenství; Female; prospektivní studie